Estimating the Amount of Water Required for Crop Irrigation Based on the Application of FAO's CROPWAT Program in the Case of Kashkadarya Region - Abdullaev Botirjon; Razzakov Ruslan; Nasibov Boburbek; Mukhamedov Gayrat; Aytmuratov Timurlan; Dadajonov Boburjon (BIO Web of Conferences)
The article calculates the amount of water required for irrigation in the irrigated areas of Kashkadarya region based on the climate change conditions using the cropwat program of FAO. The standard evapotranspiration was calculated taking into account the climate data and the stable factors of the plant and weather conditions. In CLIMWAT 2.0, the climate indicators are monthly averages of effective precipitation based on multiyear data from the USDA Soil Conservation Service of the United States Department of Agriculture. Service) calculated as follows using the formula. The water demand of the agricultural crops grown in the experimental plots was calculated. The granulometric composition of soil samples was determined using the soil structure triangle (also known as the Ferret triangle) developed by the US Department of Agriculture (USDA). Using the CROPWAT program, irrigation rates, number of irrigations and total irrigation rates were calculated for the cotton crop placed in the research facility. Based on the application of the FAO UN CROPWAT program, the one-time irrigation standards for the cotton crop are 700-930 m3/ha, the number of irrigations is 7 times and the seasonal irrigation standard is 6400 m3/ha, in the usual way, that is, when calculated on the basis of II- hydromodule regional indicators, the one-time irrigation standards are 700- 930 m3/ha, the number of irrigations is 9 times, and the seasonal irrigation standard is 7100 m3/ha and the indicators were close to each other. This indicates that the calculations are done correctly.